A Systematic Review of Osteoporosis Health Beliefs in Adult Men and Women. (25th July 2011) - McLeod, Katherine M.; Johnson, C. Shanthi
Abstract : Osteoporosis is major public health concern affecting millions of older adults worldwide. A systematic review was carried out to identify the most common osteoporosis health beliefs in adult men and women from descriptive and intervention studies. The Osteoporosis Health Belief Scale (OHBS) and Osteoporosis Self-efficacy Scale (OSES) evaluate osteoporosis health beliefs, including perceived susceptibility and seriousness, benefits, barriers, and self-efficacy of calcium and exercise, and health motivation, and their relationship to preventive health behaviours. A comprehensive search of studies that included OHBS and OSES subscale scores as outcomes was performed. Fifty full-text articles for citations were reviewed based on inclusion criteria. Twenty-two articles met the inclusion criteria. Greater perceived seriousness, benefits, self-efficacy, health motivation, and fewer barriers were the most common health-belief subscales in men and women. Few studies were interventions (n = 6 ) and addressed osteoporosis health beliefs in men (n = 8 ). Taking health beliefs into consideration when planning and conducting education interventions may be useful in both research and practice for osteoporosis prevention and management; however, more research in this area is needed.